2013
DOI: 10.1002/eat.22129
|View full text |Cite
|
Sign up to set email alerts
|

Reduced fasting plasma levels of diazepam‐binding inhibitor in adolescents with anorexia nervosa

Abstract: These data further extend our knowledge of neuropeptide dysfunction in AN, and plasma DBI may represent a marker for this disease, in particular considering its correlation with comorbid mood disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 22 publications
2
24
2
Order By: Relevance
“…1) was very low, implying that an extremely high number of subjects should have been recruited to demonstrate a putative difference in plasma DBI levels between patients and controls. Moreover, fasting DBI plasma levels were very similar with respect to those obtained in another series of 10 age-comparable healthy controls [20]. Concomitantly, we showed that DHEA-S is significantly increased and, since cortisol (8.00 a.m.) was not changed, the CDR was inevitably reduced in BPD patients with respect to healthy controls.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…1) was very low, implying that an extremely high number of subjects should have been recruited to demonstrate a putative difference in plasma DBI levels between patients and controls. Moreover, fasting DBI plasma levels were very similar with respect to those obtained in another series of 10 age-comparable healthy controls [20]. Concomitantly, we showed that DHEA-S is significantly increased and, since cortisol (8.00 a.m.) was not changed, the CDR was inevitably reduced in BPD patients with respect to healthy controls.…”
Section: Discussionsupporting
confidence: 59%
“…DBI plasma levels were assessed in duplicate by commercial human ELISA kits (AbFrontier; DBI capture antibody: 2F2, DBI detector antibody: biotin-27C9) and expressed in nanograms per millilitre. Intra-assay and interassay variabilities were below 10%, and the readings were all within the linear part of the standard curve, as previously shown [20]. …”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…Laboratory investigations were carried out blindly with respect to clinical data. Leptin plasma levels were assessed by commercial human ELISA kits (DRG Diagnostics [7]). Aβ40 and Aβ42 plasma levels were determined in duplicate using a commercially available ELISA kit (Millipore) and expressed in picograms per millilitre, as previously reported [16].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Aβ and other APP fragments play a role in the physiology of synaptic transmission, neuronal migration and outgrowth [4,5], suggesting that a dysfunction of Aβ signalling might be potentially operative in those synaptopathies expressing without overt neurodegenerative phenomena, as most psychiatric diseases are thought to be [6]. AN patients, in particular, display neuropsychiatric dysfunctions beyond the core ones related with eating behaviour, including, among others, mood [7] or memory impairment [8], both involving altered connectivity within brain networks [9]. Synaptic dysfunction has never been consistently investigated in AN patients, but experimental evidence derived from animal models of activity-based anorexia supports this assumption [10].…”
Section: Introductionmentioning
confidence: 99%